Analisis Determinan Profit Distribution Management Bank Umum Syariah Periode 2013-2016 - Alteza, Muniya (Li Falah: Journal of Islamic Economics and Business, 2017)
This study aimed to examine the variables as determinant of Profit Distribution Management of theSharia Commercial Bank in Indonesia in the 2013-2016 periods. The variables studied consisted ofthe proportion of third party funds, the effectiveness of third party funds, the capital adequacy ratioand the ratio of operational costs to operating income. Samples were collected using purposivesampling technique. Data analysis technique used is multiple linear regression. The results showedthat the proportion of third party funds, the effectiveness of third party funds which was proxied byFinancing to Deposit Ratio (FDR) and Capital Adequacy Ratio (CAR) individually had a positiveand significant effect on Profit Distribution Management. In addition it was found that the ratio ofoperational costs to operating income (BOPO) had no significant effect on Profit DistributionManagement. The value of Adjusted R2 was 0,254 which means that variation of Profit DistributionManagement which can be explained by variable used in research was 25,4% while the rest equal to74,6% explained by other variables not used in the model of this research.